LEVERAGE SEBAGAI VARIABEL MODERATING PENGARUH TAX MINIMIZATION TERHADAP TRANSFER PRICING PERUSAHAAN MULTINASIONAL - Catur Adi Nugroho; R.A Norromadani Yuniati; Irma Rustini Aju (Program Studi D4-Manajemen Bisnis, Jurusan Teknik Bangunan Kapal, Politeknik Perkapalan Negeri Surabaya, 2022)
The value of international trade in Indonesia shows an increasing trend in 2015-2021. This should be able to increase international trade tax revenues. However, the state has the potential to lose tax revenues due to transfer pricing practices. This study aims to axamine and analyze leverage as a moderating variable of the effect tax minimization on transfer pricing of multinational companies. This study uses quantitative data. The object of research is the energy, infrastructure, transportation and logistics sector companies listed on the Indonesia Stock Exchange for the 2015-2021 period. Sampling used purposive sampling technique so that eight multinational companies were obtained as research samples. Data were analyzed using Moderated Regression Analysis and simple regression analysis. The result show that tax minimization has a positive effect on transfer pricing decisions. The existence of asymmetric information makes management take advantage of gaps in tax regulations between different countries to decide on transfer pricing. Leverage moderates the effect of tax minimization on transfer pricing decisions. Positive accounting theory explains that companies that have debt will be more aggressive in tax minimization.